(untitled) (Journal of Applied Business and Economics, 2022)
This paper analyzes the evolution of foreign capital entry into the Russian banking system and documents the current characteristics and lending behavior of 100% foreign-owned banks in Russia. Using the lessons from the recent rapid foreign banking expansion in Russia, I show that the liberalization of Russia’s banking system and the attractiveness of its market opportunities were essential determinants for foreign bank entry. I find that country of origin matters in foreign bank lending preferences. In general, foreign banks from developed home countries focus on lending to Russian corporate customers while foreign banks from emerging markets follow the "follow the customer" strategy.